Pengaruh Pemanfaatan Manajemen Pemasaran Online terhadap Keberhasilan UMKM dalam Mengembangkan Usahanya (Studi Kasus Handsqob.id) - Pramudita, Ika Dwi Pramudita; Julianti, Mira; Ameliya, Ameliya; Fresty, Kharismah; Sari, Dian Puji Puspita (BISMA : Business and Management Journal, 2024)
The use of online marketing management has become an important strategy for Micro, Small and Medium Enterprises (MSMEs) in expanding their market reach and increasing the success of their businesses in the digital era. This study uses a qualitative approach with in-depth interviews as the primary data collection method. The research results show that Handsqob.id has succeeded in increasing the visibility of its products through the use of e-commerce platforms such as Shopee and TikTok Shop and being active on social media such as Instagram. Measurable marketing strategies, such as SEO optimization, attractive visual content, collaboration with influencers, and targeted promotions, have helped Handsqob.id in increasing sales and brand awareness. Challenges faced, such as intense competition and efficient operational management, are also discussed in this article as part of the overall analysis. The implications of this research suggest that other MSMEs can adopt these best practices to increase their success and growth in today's digital marketplace.